A long‐lived Aβ oligomer resistant to fibrillization. Issue 8 (10th January 2018) - Nick, Mimi; Wu, Yibing; Schmidt, Nathan W.; Prusiner, Stanley B.; Stöhr, Jan; DeGrado, William F.
Abstract: The hydrophobic Aβ peptide is highly aggregation prone; it first forms soluble oligomers, which then convert into the amyloid fibrils found in the cerebral plaques of Alzheimer's disease. It is generally understood that as the peptide concentration of Aβ increases, the fibrillization process is accelerated, but we examine the limits on this phenomenon. We found that once a threshold concentration of Aβ is exceeded, a stable oligomer is formed at the expense of fibril formation. The suppression of fibril formation was observed by amyloid‐binding dye Thioflavin T and solution nuclear magnetic resonance (NMR). Small‐angle X‐ray scattering, size exclusion chromatography, and analytical ultracentrifugation demonstrated that Aβ peptides form a range of compact species, with a dimer being an early highly populated oligomer. Solution NMR allowed us to define the secondary structure of this Aβ dimer, which shows interlocking contacts between C‐terminal peptide strands. Thus, we present a novel Aβ oligomer that resists conversion to fibrils and remains stable for more than one year. Abstract :